Efficacy of platelet-rich fibrin on socket healing after mandibular third molar extractions. Issue 4 (July 2021) - Fujioka-Kobayashi, Masako; Miron, Richard J.; Moraschini, Vittorio; Zhang, Yufeng; Gruber, Reinhard; Wang, Hom-Lay
Abstract: Objective: To investigate the efficacy of platelet-rich fibrin (PRF) for the socket healing after removal of mandibular third molars when compared to natural wound healing. Methods: This systematic review and meta-analysis were conducted according to PRISMA guidelines. The eligibility criteria comprised randomized controlled trials (RCTs) comparing the clinical outcomes of PRF with that of natural healing. Outcomes measured include post-operative pain, analgesics taken, swelling, soft tissue healing, bone healing, complication rates, as well as incidence of alveolar osteitis (AO, dry socket). Results: From 194 articles identified, 18 RCTs were included. Overall, 15 of 18 RCTs demonstrated significantly better outcomes in terms of reduced complication rates, healing rates, or patient reported pain scores in the PRF group when compared to control. Data from all studies demonstrated that PRF was able to significantly lower the rate of AO from 15.9 % in the control group to 5.8 % in the PRF group, representing a ∼3-fold reduction. All studied investigating soft tissue healing with PRF demonstrated better outcomes in favor of PRF group. Conclusions: PRF was shown to decrease post-op pain/morbidity, have favored soft tissue healing, and possess lower complication rates or AO incidence. PRF therefore proves to be a viable treatment adjunct following removal of mandibular third molars.